Evaluation of serological response to anti-SARS-CoV-2 mRNA vaccination in hematological patients - Pascale, Sara Pasquina; Nuccorini, Roberta; Pierri, Teresa; Di Mare, Roberta; Fabio, Lucia; Lerose, Emilia; Merlino, Maria Antonietta; Schiavo, Pietro; Amendola, Angela; Brucoli, Gino; Caputo, Maria Denise; Chitarrelli, Ida; et al. (Frontiers in Immunology, 2022)
Introduction In immunocompromised patients, SARS-COV-2 mRNA vaccine has been used in Italy from the beginning of vaccination campaign, but several studies have shown that serological response of onco-hematological patients was reduced compared to healthy subjects, due to the state of immunosuppression because of both underlying disease and administered therapy. Methods We evaluated the association of anti-SARS-COV-2 spike IgG titer in 215 haematological patients with clinical and demographic variables to verify if it was possible to identify predictive parameters of serological response, as well as using a control group, consisting of healthy health workers of San Carlo Hospital in Potenza. IgG titers anti-SARS-CoV2 were evaluated after 30-45 days post booster using chemiluminescent microparticle immunoassay technology. Results Patients with hematological malignancies, compared with the control arm, had both a mean concentration of anti-SARS-CoV2 IgG significantly lower and a seroconversion rate numerically lower. All Chronic Lymphatic Leukemia patients showed levels of antibody titer below the mean concentration, also in only clinical surveillance patients. Comparing serological response in hematological malignancies, only Acute Leukemia patients who were off therapy had highest seroconversion rate among the patients’ cohorts and a mean antibody concentration greater than control arm. Patients treated with steroids and Rituximab showed a lower level of anti-SARS-COV-2 spike IgG. Differences of anti-spike IgG levels among Chronic Myeloid Leukemia patients stratified according to TKI therapy and molecular response were observed and they could have interesting implications on the evaluation of the effects of these drugs on the immune system, but, having not reached statistically significance at the moment. The cohort of patients who received a stem cell transplant was very heterogeneous because it included different hematological malignancies and different types of transplant, however a mean concentration of anti-SARS-CoV2 IgG greater than the control arm was reported. Indeed among patients who performed a transplant for over 6 months only one had a spike IgG titer below the cutoff. Conclusions Our data confirm reduced serological response in haematological patients after anti-SARS-COV-2 vaccination. However, a great diversity of response according to types of pathologies and therapies raises.